Analisis Self Disclosure Transpuan di Kota Semarang dalam Mengungkapkan Jati Dirinya Melalui Komunikasi Interpersonal - Sunarto, Rhetta (Universitas Batanghari Jambi, 2025)
The aim of this research is to analyze the self-disclosure of transwomen in Semarang City in expressing their identity through interpersonal communication. This qualitative research uses descriptive qualitative methods. Primary data collection is through observation and interviews, while secondary data collection is through literature study. The results of this research reveal that trans women in Semarang City carry out in-depth interpersonal communication with their friends and community. There are 4 (four) factors that are indicators of self-disclosure of transwomen in the City of Semarang, namely: clichés, facts, opinions and feelings and educational and economic factors that influence the self-confidence of transwomen in the City of Semarang.